Impact Of An Educational Intervention On Community Residents’ Knowledge, Attitudes And Perceptions Regarding Antibiotics And Antibiotic Resistance In Jelutong District, Penang, Malaysia - Irawati, Lyna (2018)
To combat antibiotic resistance (ABR), the World Health Organization (WHO) urges all nations to increase public knowledge of antibiotics and ABR. In Malaysia, there is a paucity of data regarding the impact of educational interventions on community residents’ knowledge, attitudes and perceptions in relation to antibiotics and ABR. Therefore, this research project aimed to explore and assess community residents’ knowledge, attitudes and perceptions regarding antibiotics and ABR in Jelutong District, Penang, Malaysia. It also aimed to develop and implement an educational intervention to increase residents’ knowledge and change their attitudes towards and perceptions of antibiotics and ABR.